2018
DOI: 10.1016/j.bjid.2017.12.003
|View full text |Cite
|
Sign up to set email alerts
|

First case of Furuncular Myiasis due to Cordylobia anthropophaga in a Latin American resident returning from Central African Republic

Abstract: Myiasis is a temporary infection of the skin or other organs with fly larvae. The larvae develop into boil-like lesions. Creeping sensations and pain are usually described by patients. Following the maturation of the larvae, spontaneous exiting and healing is experienced. Herein we present a case of a traveler returning from Central African Republic. She does not recall insect bites. She never took off her clothing for recreational bathing, nor did she visit any rural areas. The lesions appeared on unexposed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
0
5
0
2
Order By: Relevance
“…Dehecq and colleauges [ 34 ] manually extracted two larvae from a 9-month-old boy and the lesions healed shortly after extraction [ 23 , 66 ]. There was 45.3% of the reviewed literature which used manual extraction to successfully remove larvae [ 9 , 17 , 30 , 33 , 36 , 37 ]. None of these cases reported larval fragmentation during the extraction process.…”
Section: Discussionmentioning
confidence: 99%
“…Dehecq and colleauges [ 34 ] manually extracted two larvae from a 9-month-old boy and the lesions healed shortly after extraction [ 23 , 66 ]. There was 45.3% of the reviewed literature which used manual extraction to successfully remove larvae [ 9 , 17 , 30 , 33 , 36 , 37 ]. None of these cases reported larval fragmentation during the extraction process.…”
Section: Discussionmentioning
confidence: 99%
“…Os principais agentes da miíase cutânea furunculoide são Dermatobia hominis, Cordylobia anthropophaga, Cuterebra sp e Wohlfahrtia sp. 4,5 É mais comum em países em desenvolvimento (intertropicais), como os da América Central, América do Sul e África subsaariana. 6 Os casos incidentes em indivíduos provenientes de outras áreas do globo decorrem, em geral, de viajantes que estiveram em área endêmica, imputando grande desafio diagnóstico ao retornarem ao país de origem.…”
Section: Discussionunclassified
“…7,8 Em geral, a extração manual da larva não representa um desafio e é facilitada pela oclusão do orifício com substâncias petrolizadas. 5 Entretanto, quando o diagnóstico da lesão não é realizado corretamente ou quando a larva não é estruída (espontaneamente ou sob manipulação), pode evoluir para a formação de uma tumoração que simula um cisto epidérmico, lipoma (como o caso apresentado) ou mesmo neoplasias malignas de partes moles. 10,11 Nestes casos, a única conduta efetiva é a exérese cirúrgica.…”
Section: Discussionunclassified
“…We read the publication by Suárez et al on “First case of Furuncular Myiasis due to Cordylobia anthropophaga in a Latin American resident returning from Central African Republic” with great interest. 1 Suárez et al noted that “ To our knowledge, this is the first reported case of C. anthropophaga in Latin America. 1 ” The interesting question is whether this is an exact first case of C. anthropophaga in Latin America.…”
mentioning
confidence: 89%
“… 1 Suárez et al noted that “ To our knowledge, this is the first reported case of C. anthropophaga in Latin America. 1 ” The interesting question is whether this is an exact first case of C. anthropophaga in Latin America. In fact, the myiasis is not an uncommon problem and might relate to the travel to endemic area.…”
mentioning
confidence: 89%